MEMBANGUN KESADARAN ETIS MELALUI PENDEKATAN HOLISTIK: PENGARUH CERITA BERGAMBAR DAN ROLE-PLAYING DALAM PEMBELAJARAN PKn TERHADAP PENCEGAHAN KORUPSI USIA DINI - Aang Supriatna; Ratna Fitria; Rika Sartika; Intan Indah Megasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the influence of picture story media and role-playing method in Civics Education on early corruption prevention through building ethical awareness in elementary school students. Using a quantitative approach with quasi-experimental nonequivalent control group design, this research involved 62 fourth-grade students divided into experimental and control groups. Data were collected through ethical awareness questionnaires and observation sheets, then analyzed using independent sample t-test and N-Gain analysis. The results showed that the holistic approach combining picture stories and role-playing had a significant influence on students' ethical awareness (t-count 4.32 > t-table 2.00) with an N-Gain score of 0.68 in the medium category. The integration of visual narratives and experiential learning through role-playing enabled students to internalize anti-corruption values such as honesty, responsibility, and care for public goods more effectively compared to conventional methods. This research contributes to the development of innovative Civics Education learning models oriented toward character building and early corruption prevention in elementary schools.